PENYELESAIAN SENGKETA TANAH HAK ULAYATSUKU DAYAK KAMPUNG 10 UPAU, KABUPATEN TABALONG KALIMANTAN SELATAN - Tanjung Diyah Kusumaningrum, Sukirno, Triyono (Diponegoro Law Journal, 2012)
Land has meaning and role that is essential for human life, because everyone needs the land to death in his lifetime and considering the composition of life and economic patterns that are patterned largely agrarian. The importance of human relationships with the land other than in relation to the law, the common law has a cosmic connection-magical-religious. This relationship is not between the individual and the land, but also among a group of members of the public a partnership law (rechtgemeentschap) in relation to land rights. The purpose of research to find out what the reasons behind the emergence of land rights disputes of the Dayak village 10 Upau, Tabalong Regency South Kalimantan and the process and procedures used by the parties to the settlement of land disputes Tabalong customary rights in the District of South Kalimantan.   The authors conducted this study using the juridical approach to the specification of empirical research that is descriptive analysis. Data collection techniques used are dipeoleh primary data through interviews and secondary data consisting of primary legal materials in the form of laws and regulations relating to the object studied, secondary legal materials in the form of books, papers and legal materials tertiary in the form of a dictionary Indonesian and English Dictionary. The data obtained and analyzed qualitatively.   Based on the survey results revealed that the reasons behind the occurrence of land disputes H. Nana Thamrin (the plaintiff) by Toto Darsani Kornelis, as defendant; Melky Satria, as a defendant II; Kopari Adi, as Defendant III; Ardiansyah, as Defendants IV; Patmadi, as Defendants V; Rusdianto, as Defendants VI; June Latu Day , for Defendant VII; Ardianto, as a defendant VIII; Rully A., as a defendant IX; Ramdhani, as defendants X and PT. ADARO INDONESIA, as a defendant XI. On seat case, including: (a) That the plaintiff is the legal owner of land the size of an area of approximately 122 hectares (one hundred and twenty-two hectares) located in the village of Lok Stone (RiverMarim) district. Haruai Kab. Tabalong borders: East by land PT. Jewel Cakung Nusa North with: land PT. Cakung Nusa gem, the west: land PT. Cakung Nusa gem, south by: soil communities. (B) That the plaintiff's land was acquired by way of purchase, ie: buy Maswar Puguh Prayudi of approximately 79 hectares (seventy-nine acres) as Sales and Purchase Statement dated May 15, 2009 and purchases by residents of approximately 40 hectares ( forty hectares) as in the Statement / Receipt. Lokbatu dated June 5, 2009. (C) That the actions of the Defendants (I, II, III, IV, V, VI.VII, VIII, IX, X and XI) are bought and sold property master CLAIMANT is no right of action and arbitrary, it The lead plaintiff has suffered loss of both material as well as immaterielm.   The process of customary rights land disputes through the District Court Tabalong South Kalimantan. The result of the District Court of the Cape include: (a) grant the Plaintiffs claim for some. (B) declare that the Plaintiff is the rightful owner of the land size of approximately 34 hectares (thirty four hectares) located in the village of Lok Rocks Territory (river Marim) district. Haruai Kab. Tabalong borders: East by land PT. Jewel Cakung Nusa North with: land PT. Cakung Nusa gem, the west: land PT. Cakung Nusa gem, south with: community land sebagimana exhibit P-2 through P-28 (c) declare the act Defendant I, Defendant II, Defendant III, Defendant IV, Defendant V, VI Defendant, Defendant VII, VIII Defendants, Defendant IX, Defendants X and XI Defendant committed an unlawful act (onrechtmatige DAAD) (d) Refuse lawsuit plaintiff to besides and beyond (e) To punish Defendant I, Defendant II, Defendant III, Defendant IV, V Defendant, Defendant VI, VII Defendants, Defendant VIII, IX Defendant, Defendant X and XI Defendants to pay the legal costs jointly and severally for Rp.6.821.000, - (six million eight hundred twenty one thousand Rupiah).